The Relationship between Maternal Knowledge and Attitudes About Growth and Development with Maternal Behavior of Conducting Sdidtk in the Working Area of Puskesmas Tanjung Sakti Lahat Regency in 2023 - Riani, Ayut; Samidah, Ida; Situmorang, Ronalen (Universitas Dehasen Bengkulu, 2024)
Children are the next generation of the nation, so the quality of the next generation depends on the quality of child development, especially in infants aged three years (toddlers), because the first three years of life. Monitoring the growth and development of toddlers is very important to determine the presence of growth disorders (growth faltering) early. To achieve effective interactions between mothers and children, mothers must pay attention to their attitudes because attitudes arise from interactions in understanding, feeling and behaving on an object that is valued positively and negatively.The purpose of this study was to determine the relationship between maternal knowledge and attitudes about child growth and development with maternal behavior of conducting SDIDTK in the Working Area of the Tanjung Sakti Health Center, Lahat Regency in 2023.This type of research is analytical observational with a cross sectional design. The number of samples of this study was 81 respondents selected by purposive sampling technique. The instrument used was a questionnaire. Data were analyzed using the chi-square test. The results showed that most respondents (63.4%) had good knowledge, supportive attitudes (70.4%) and good behavior (58%) towards the implementation of SDIDTK. There is a relationship between maternal knowledge and attitudes with maternal behavior to implement SDIDTK in children with a p value of 0.000. The results of this study should be used by the community as information material, and can provide knowledge about early detection of child growth and developmen